Vacancy, Search, and Prices in a Housing Market Matching Model - Wheaton, William C. (Journal of Political Economy, 1990)
A model of the single-family housing market is proposed in which households that move are both buyers and sellers. Households move when a stochastic process leaves them dissatisifed with their current unit. Household buyers expend costly search effort to find a better house, while sellers hold two units until a buyer is found. The vacancy rate, fixed in the short run, determines the expected length of sale and search, which play a central role in the reservation prices of buyer and seller. Market prices, the result of bargaining, lie between these two. The model yields a strong theoretical relationship (inverse) between vacancy and prices, which with competitive supply explains the existence of longer-run "structural" vacancy. Copyright 1990 by University of Chicago Press.